The Effect of Sicabox Media on Students' Scientific Thinking Ability on the Material of the Properties of Light in MI - Widiya Anggraeny A. Hrp; Nirwana Anas (Didaktika: Jurnal Kependidikan, 2024)
This study aims to reveal and analyze the effect of SICABOX learning media on the scientific thinking ability of science students in grade IV SD. This type of research is experimental research with a quantitative approach. This experimental research is classified into pre experimental form of one group pretest posttest design. The data collection techniques used are interviews, observations, documentation and tests (pretest and posttest). The data analysis technique used is descriptive analysis to calculate the mean, median, mode, standard deviation, and variance. Requirements analysis with normality test, homogeneity test, and through independent t-test. The results of the study using the t-test state that the results of the posttest hypothesis test calculation obtained a sig. (tailed) value of 0.001 <0.05, it can be concluded that there is a difference in the average student learning outcomes between the control class and the experimental class. In other words, we can conclude that SICABOX media has an effect on students' scientific thinking. I recommend this paper to develop critical thinking and problemsolving aspects.